Dark personality on the background of a dark era? (On the ministry of Archbishop Varnava at the Tobolsk department in 1914–1917) - I. V. Petrov; A. S. Puchenkov (Омский научный вестник: Серия "Общество. История. Современность")
The article analyzes the monograph of P. V. Belous «Tobolsk diocese during the First World War (1914–1918)». The innovation of the work and many of its conceptual features were noted. They were achieved by attracting a wide source base. It is indicated that special attention in the monograph is given to Archbishop Varnava (Nakropin), one of the most controversial hierarchs at the final stage of the synodal period in the history of the Russian Orthodox Church